Understanding Postgraduate Student Preferences for University Choice in Zambia: The Case of ZCAS University - Kayombo, Kelvin Mukolo; Mudenda, Gwebente; Mweemba, Burton; Nduli, Janis (Journal of Education and Vocational Research, 2020)
The aim of this study was to ascertain the university brand model that characterizes postgraduate student choice of ZCAS University. The brand model comprises brand attributes that attract postgraduate students to the university, the information sources they consult, who influences their decisions and what makes the university unique. The study was qualitative in design, while sampling of research participants was done purposively. Three focus group discussions involving seventeen first years part time and open distance e-learning postgraduate students, and five semi-structured interviews with marketing and recruitment staff at ZCAS University were used to collect data on the brand model. Thematic analysis and content analysis were then used as the primary data analysis techniques. Results of the study revealed that reputation, teaching quality, student support, fees and facilities were the top five ZCAS University brand traits that underpin postgraduate students’ choice of the university. With respect to competitive advantage, facilities, teaching quality reputation and accreditations are perceived to be the university’s primary unique characteristics. The study further identified friends, self, workmate and family as the greatest influencers of postgraduate student choice of the university; while websites, social media, print media and television are believed to be the most consulted information sources by prospective postgraduate students.